1986
DOI: 10.1016/s0022-5347(17)45975-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Bladder Tumors in Organ Culture

Abstract: We have established a reliable method for culturing transitional cell tumors of the human urinary bladder. Out of seventy-four set up in culture, forty-eight were successfully maintained and their behavior studied using metaphase arrest and 125IUdR uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The model validated in this study resembled that described by Lawson et al. [17] in which tumours were cultured at the interface between medium and gas and the three‐dimensional integrity of the tissue is maintained. Serum is a vital component in media sustaining human cultures, by providing cells with complexes of conventional hormones and growth factors which are required in undefined levels.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The model validated in this study resembled that described by Lawson et al. [17] in which tumours were cultured at the interface between medium and gas and the three‐dimensional integrity of the tissue is maintained. Serum is a vital component in media sustaining human cultures, by providing cells with complexes of conventional hormones and growth factors which are required in undefined levels.…”
Section: Discussionsupporting
confidence: 63%
“…This study validated an ex vivo model which was then used to examine the apoptotic response in 41 bladder tumours after exposure to MMC. Previous studies have reported that it is possible to culture bladder tumours as explants, with success in 70–90% of moderately and poorly differentiated superficial tumours [14–18]. The advantage of explant models over single‐cell suspension culture systems is the preservation of tissue structural organization, cell‐to‐cell contacts and cell heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro bladder cancer culture systems, in addition to our own, have been developed in recent years [Leighton et al, 1977;Abaza et al, 1978;Bulbul et al, 1986;[Reese et al, 1976;Leighton and Tchao, 1984;Leighton et al, 1985;Lawson et al, 1986;Leighton, 1991;Crook et al, 20001. These systems provide a unique approach for defining key genetic and epigenetic events associated with the development of bladder cancer in pure populations of tumor cells.…”
Section: 2 Pathologymentioning
confidence: 99%
“…The single-cell suspension culture requires a thorough digestion and excludes the use of tissue explants as cell source [Lindert and Terris, 2000;Reznikoff et al, 19831. Other culture systems, such as organ culture, gradient culture, and matrix culture, have been used with bladder cancers to test cytotoxic agents at clinically relevant concentrations [Leighton et al, 1977;Abaza et al, 1978;Bulbul et al, 1986;Reese et al, 1976;Lawson et al, 1986;Crook et al, 20001. …”
Section: Single-cell Suspension Culture and Other Culture Techniquesmentioning
confidence: 99%